Risk factors affecting intradialytic hypertension in hemodialysis patients - Nugroho, Heryanto Adi; Lazuardi, Nugroho (South East Asia Nursing Research, 2021)
Hemodialysis is a CKD therapy that functions as a kidney replacement. The side effect that often occurs when patients undergoing hemodialysis is intradialytic hypertension (HID), namely an increase in systolic blood pressure >10 mmHg during hemodialysis, due to an increase in cardiac output mediated by volume overload, especially in patients with excess body weight and cardiac dilatation. The objective of this research is to determine the risk factors that influence the occurrence of intradialytic hypertension in CKD patients undergoing hemodialysis at Tugurejo Hospital. Risk factors consist of age, duration of hemodialysis, Quick Blood (blood velocity), ultrafiltration (volume overload), URR. The design used in this research is analytic observational with a cross-sectional approach, the number of respondents is 53 people. The sampling technique used in this research is total sampling. The results showed that age (p-value = < 0.01), duration of hemodialysis (p-value = 0.07), quick blood (p-value = 0.06), ultrafiltration (p-value = 0.04), and URR (p-value = < 0.01) is a protective factor or risk factor for the incidence of intradialytic hypertension. Based on the Spearman rank test, it is known that p-value > means that there is a relationship between age, ultrafiltration and URR with the blood pressure of patients with chronic kidney failure. Age, ultrafiltration, and URR are protective factors or risk factors that influence the incidence of intradialytic hypertension